Endothelial Notch1 Is Required for Proper Development of the Semilunar Valves and Cardiac Outflow Tract. Issue 4 (April 2016) - Koenig, Sara N.; Bosse, Kevin; Majumdar, Uddalak; Bonachea, Elizabeth M.; Radtke, Freddy; Garg, Vidu
Abstract : Background: Congenital heart disease is the most common type of birth defect, affecting ≈2% of the population. Malformations involving the cardiac outflow tract and semilunar valves account for >50% of these cases predominantly because of a bicuspid aortic valve, which has an estimated prevalence of 1% in the population. We previously reported that mutations in NOTCH1 were a cause of bicuspid aortic valve in nonsyndromic autosomal‐dominant human pedigrees. Subsequently, we described a highly penetrant mouse model of aortic valve disease, consisting of a bicuspid aortic valve with thickened cusps and associated stenosis and regurgitation, in Notch1 ‐haploinsufficient adult mice backcrossed into a Nos3 ‐null background. Methods and Results: Here, we described the congenital cardiac abnormalities in Notch1 +/− ;Nos3 −/− embryos that led to ≈65% lethality by postnatal day 10. Although expected Mendelian ratios of Notch1 +/− ;Nos3 −/− embryos were found at embryonic day 18.5, histological examination revealed thickened, malformed semilunar valve leaflets accompanied by additional anomalies of the cardiac outflow tract including ventricular septal defects and overriding aorta. The aortic valve leaflets of Notch1 +/− ;Nos3 −/− embryos at embryonic day 15.5 were significantly thicker than controls, consistent with a defect in remodeling of the semilunar valve cushions. In addition, we generated mice haploinsufficient for Notch1 specifically in endothelial and endothelial‐derived cells in a Nos3 ‐null background and found that Notch1 fl /+ ; Tie2‐Cre +/− ;Nos3 −/− mice recapitulate the congenital cardiac phenotype of Notch1 +/− ;Nos3 −/− embryos. Conclusions: Our data demonstrate the role of endothelial Notch1 in the proper development of the semilunar valves and cardiac outflow tract.